Optogenetic cleavage of the Miro GTPase reveals the direct consequences of real-time loss of function in Drosophila. - Francesca Mattedi; Ethlyn Lloyd-Morris; Frank Hirth; Alessio Vagnoni (PLoS Biology)
Miro GTPases control mitochondrial morphology, calcium homeostasis, and regulate mitochondrial distribution by mediating their attachment to the kinesin and dynein motor complex. It is not clear, however, how Miro proteins spatially and temporally integrate their function as acute disruption of protein function has not been performed. To address this issue, we have developed an optogenetic loss of function "Split-Miro" allele for precise control of Miro-dependent mitochondrial functions in Drosophila. Rapid optogenetic cleavage of Split-Miro leads to a striking rearrangement of the mitochondrial network, which is mediated by mitochondrial interaction with the microtubules. Unexpectedly, this treatment did not impact the ability of mitochondria to buffer calcium or their association with the endoplasmic reticulum. While Split-Miro overexpression is sufficient to augment mitochondrial motility, sustained photocleavage shows that Split-Miro is surprisingly dispensable to maintain elevated mitochondrial processivity. In adult fly neurons in vivo, Split-Miro photocleavage affects both mitochondrial trafficking and neuronal activity. Furthermore, functional replacement of endogenous Miro with Split-Miro identifies its essential role in the regulation of locomotor activity in adult flies, demonstrating the feasibility of tuning animal behaviour by real-time loss of protein function.